Sources of Inflation in Developing Countries - Loungani, Prakash; Swagel, Phillip (Washington, D.C. : International Monetary Fund, 2001)
This paper develops stylized facts about the inflation process in developing countries, focusing particularly on the relationship between the exchange rate regime and the sources of inflation. Using annual data from 1964 to 1998 for 53 developing countries, we find that money growth and exchange rate changes-factors typically related to fiscal influences-are far more important in countries with floating exchange rate regimes than in those with fixed exchange rates. Instead, inertial factors dominate the inflation process in developing countries with fixed exchange rate regimes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet